2014
DOI: 10.18553/jmcp.2014.20.12.1236
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Annual Drug Costs of Biologic Therapies Across Indications from the Humana Commercial Database

Abstract: BACKGROUND: A variety of biologic therapies are currently used for the treatment of inflammatory autoimmune diseases, including rheumatoid arthritis (RA), psoriasis (PsO), psoriatic arthritis (PsA), and ankylosing spondylitis (AS). These diseases require long-term treatment, and information regarding the use and costs of biologic therapies can be valuable in making treatment and formulary decisions for clinicians and payers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
63
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 9 publications
13
63
1
2
Order By: Relevance
“…The current study results are consistent with previous studies that found that etanercept and adalimumab were the most frequently administered TNFis in patients with AS [22,24,31]. This may be because these drugs were among the first TNFis approved by the US FDA for the treatment of AS and because of formulary availability and insurance contracts.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study results are consistent with previous studies that found that etanercept and adalimumab were the most frequently administered TNFis in patients with AS [22,24,31]. This may be because these drugs were among the first TNFis approved by the US FDA for the treatment of AS and because of formulary availability and insurance contracts.…”
Section: Discussionsupporting
confidence: 92%
“…TNFi-iv. In the findings reported here, the discontinuation rate (31%) was similar to the discontinuation rate (34%) in a previous study of TNFis in patients with AS [23]; however, the rate of switching to a new TNFi (21%) fell between the results of previous studies (4-30%) [23,24,32]. Previous studies have confirmed that while switching to a second TNFi can be effective in AS, overall effectiveness may be somewhat lower [21,33,34].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To achieve this, a unique methodology was developed to operationalize evaluation of TNFi dose stability, which is robust to the claim source (pharmacy or medical). This methodology was adapted from previously published methods used for the identification of treatment patterns and costs of TNFi in other diseases [13], in addition to previously published investigations of HCRU and cost in UC [8,9,14]. In contrast to other methodologies, patients with UC in this study were categorized quarterly into four mutually exclusive treatment pattern groups during the maintenance phase.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of etanercept in combination with MTX was proven in recent literature, where etanercept demonstrated beneficial effects, such as radiological and clinical responses (20,21,24).Our results indicate that the total cost of treating RA with etanercept in combination with MTX is on average 1.509.533, 002 RSD (12.178, 26 Euro), which is lower than the results from the USA (25)(26)(27). Due to the high costs of bDMARDs, the use of etanercept or similar drugs within the Serbian health system is not part of regular clinical practice, and it is limited by restrictive guidelines, which are common in the health systems of European countries (28).…”
Section: Discussionmentioning
confidence: 46%